Short and sweet: Sustained reduction in tinnitus-related distress following intensive interdisciplinary treatment—A 5-year follow-up study - Lukas, Cosima F.; Ivansic, Daniela; Schneider, Gerlind; Lemhöfer, Christina; Guntinas-Lichius, Orlando; Dobel, Christian (Frontiers in Audiology and Otology, 2025)
IntroductionTinnitus is a chronic condition that can cause considerable psychological distress. While clinical guidelines recommend interdisciplinary treatment, long-term effects remain underexplored. This study evaluated tinnitus-related distress over a 5-year follow-up period following intensive interdisciplinary treatment in patients experiencing chronic bothersome tinnitus.MethodsThis cohort study analyzed a representative sample of patients with chronic, bothersometinnitus (n = 747) who underwent a 5-day intensive interdisciplinary treatment, including cognitive behavioral therapy, sound enrichment via hearing aids, ENT and medical rehabilitation diagnostics, and physiotherapy. Long-term follow-up assessments were conducted at an average of 5 years post-treatment with a response rate of 48%. Tinnitus-related distress was assessed using the Tinnitus Questionnaire. Data were missing completely at random.ResultsTinnitus-related distress was significantly reduced post-treatment and remained stable across follow-up measurements (p < 0.001, d = 1.33), regardless of initial symptom severity [F(10, 1, 470) = 5.6, p < 0.001, η2 = 0.02]. Psychosocial factors explained 47% of the variance in tinnitus-related distress at follow-up [F(4, 335) = 75.77, p = 0.000, R2 = 0.47].DiscussionSustained improvements in tinnitus-related distress were observed over a 5-year follow-up period after the intervention. These findings show that chronic tinnitus can be sustainably managed within a brief treatment period, emphasizing the need for personalized, interdisciplinary strategies to accommodate patient heterogeneity.